Field verification of ventilation performance and driver-area isolation in a purpose-modified taxi for transporting patients with infectious disease - Hiroko Kitamura; Yo Ishigaki; Akira Saito; Shinji Yokogawa (Annals of Work Exposures and Health, 2026)
Abstract During the COVID-19 pandemic, taxis were used to transport patients with mild symptoms; however, quantitative field evidence on ventilation performance and driver-area isolation in modified taxis remains limited. We conducted a field demonstration experiment to evaluate a purpose-modified taxi under real driving conditions: approximately constant-speed driving (55 km/h) and variable-speed driving. Rear-cabin ventilation was assessed using carbon dioxide (CO2) tracer-gas decay, and compartmental isolation was evaluated using particle measurements. Estimated air changes per hour were 33.8 h−1 during constant-speed driving and 44.8 h−1 during variable-speed driving. Rear-cabin CO2 concentrations exceeded 8,000 ppm immediately after tracer release in both runs, while front-cabin CO2 concentrations remained near background levels. Rear-cabin particle counts exceeded 12,000 counts per minute (cpm) in both runs, while front-cabin counts remained ≤15 cpm, corresponding to ≤0.12% of rear-cabin peak levels. Under the tested configuration, the modified taxi achieved high rear-cabin ventilation while maintaining strong driver-area isolation. This paired field-verification approach may support practical evaluation of exposure-control measures in purpose-modified passenger transport vehicles.